Mineralogical, crystallographic and redox features of the earliest stages of fluid alteration in CM chondrites. (15th July 2017) - Pignatelli, Isabella; Marrocchi, Yves; Mugnaioli, Enrico; Bourdelle, Franck; Gounelle, Matthieu
Abstract: The CM chondrites represent the largest group of hydrated meteorites and span a wide range of conditions, from less altered (i.e., CM2) down to heavily altered (i.e., CM1). The Paris chondrite is considered the least altered CM and thus enables the earliest stages of aqueous alteration processes to be deciphered. Here, we report results from a nanoscale study of tochilinite/cronstedtite intergrowths (TCIs) in Paris—TCIs being the emblematic secondary mineral assemblages of CM chondrites, formed from the alteration of Fe-Ni metal beads (type-I TCIs) and anhydrous silicates (type-II TCIs). We combined high-resolution transmission electron microscopy, scanning transmission X-ray microscopy and electron diffraction tomography to characterize the crystal structure, crystal chemistry and redox state of TCIs. The data obtained are useful to reconstruct the alteration conditions of Paris and to compare them with those of other meteorites. Our results show that tochilinite in Paris is characterized by a high hydroxide layer content ( n  = 2.1–2.2) regardless of the silicate precursors. When examined alongside other CMs, it appears that the hydroxide layer and iron contents of tochilinites correlate with the degree of alteration experienced by the chondrites. The Fe 3+ /ΣFe ratios of TCIs are high: 8–15% in tochilinite, 33–60% in cronstedtite and 70–80% in hydroxides. These observations suggest that alteration of CM chondrites took place under oxidizing conditions that could have been induced by significant H2 release during serpentinization. Similar results were recently reported in CR chondrites (Le Guillou et al., 2015), suggesting that the process(es) controlling the redox state of the secondary mineral assemblages were quite similar in the CM and CR parent bodies despite the different alteration conditions. According to our mineralogical and crystallographic survey, the formation of TCIs in Paris occurred at temperatures lower than 100 °C, under neutral, slightly alkaline conditions that favored the formation of both tochilinite and cronstedtite. During the course of alteration, the reduction in sulfur activity and/or the decrease of temperature prevented tochilinite crystallization and favoured the formation of cronstedtite and iron hydroxides. We suggest that iron hydroxides probably formed as ferrihydrite and then progressively converted to goethite between 50° and 80 °C, a temperature range that is also favorable for cronstedtite formation. The presence of cronstedtite plays a key role in the reconstruction of the alteration history, demonstrating that the alteration of Paris took place by way of serpentinization processes similar to those described on the Earth.